2017
DOI: 10.3945/ajcn.117.157263
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucose and insulin responses after consumption of breakfasts with different sources of soluble fiber in type 2 diabetes patients: a randomized crossover clinical trial

Abstract: Background:The amount and quality of carbohydrates are important determinants of plasma glucose after meals. Regarding fiber content, it is unclear whether the intake of soluble fibers from foods or supplements has an equally beneficial effect on lowering postprandial glucose. Objective: The aim of our study was to compare the acute effect of soluble fiber intake from foods or supplements after a common meal on postprandial plasma glucose and plasma insulin in patients with type 2 diabetes (T2D). Design: A ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 35 publications
2
42
0
2
Order By: Relevance
“…Many studies have reported that dietary fibers can slow down food digestion and nutrient absorption influencing the metabolism of carbohydrates (Chang et al, 2002;de Carvalho et al, 2017;Reverri et al, 2017). In addition to controlling blood glucose levels, dietary fibers also regulate bile acid metabolism and lipid concentrations in F I G U R E 2 Effects of pre-germinated brown rice extract on AMP-activated protein kinase, insulin receptor, insulin receptor substrate-1, insulin receptor substrate-2, peroxisome proliferator-activated receptor-γ, phosphatidylinositol-3-kinase, Akt, glucose transporter-1, glucose transporter-4, and glucokinase protein expression levels in the skeletal muscle of high-fat diet (HFD)-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that dietary fibers can slow down food digestion and nutrient absorption influencing the metabolism of carbohydrates (Chang et al, 2002;de Carvalho et al, 2017;Reverri et al, 2017). In addition to controlling blood glucose levels, dietary fibers also regulate bile acid metabolism and lipid concentrations in F I G U R E 2 Effects of pre-germinated brown rice extract on AMP-activated protein kinase, insulin receptor, insulin receptor substrate-1, insulin receptor substrate-2, peroxisome proliferator-activated receptor-γ, phosphatidylinositol-3-kinase, Akt, glucose transporter-1, glucose transporter-4, and glucokinase protein expression levels in the skeletal muscle of high-fat diet (HFD)-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Given that obese dogs frequently exhibit an impaired glycaemic response, including hyperglycaemia, hyperinsulinaemia and insulin resistance, the consumption of fermentable fibres may improve these measures across multiple meals. In addition, human studies have shown that consumption of initial meals high in fibre, especially those that are soluble and/or fermentable, can curb the glycaemic response of a high-glycaemic second meal (13)(14)(15)(16) . The overarching hypothesis is that the production of SCFA (acetate; butyrate; propionate) produced from fermentation of fibre in the large bowel modulates the observed effects by delaying gastric emptying (17) , down-regulating lipolysis in adipocytes (18) , increasing glucose utilisation in glycolysis and decreasing glucose production (19) and increasing postprandial insulin and GLP-1 production (8) .…”
mentioning
confidence: 99%
“…Fiber consumption is relevant for human health improving intestinal motility (Bernaud and Rodrigues, 2013). Besides that, it helps in the treatment of Diabetes Mellitus, reducing blood glucose (Carvalho et. al., 2017), and obesity (Post et al, 2012), contributing to reduce the risk of both cardiovascular and coronary diseases once it is related to the improvement of modifiable risk factors such as hypertension and hypercholesterolemia (Threapleton et al, 2013).…”
Section: Resultsmentioning
confidence: 99%